Data Aggregation Approach to Improve the Network Lifetime in wireless sensor networks - Dinesh, D; Rao, B. Jogeswara (International Journal of Computer Sciences and Engineering, 2025)
The core part of Wireless Sensor Networks [WSNs] is typically sensor nodes which have the ability to carefully collect sensory information, sense, consistently process the sensitive information and communicate efficiently with other connected nodes in the established network. The network lifetime will generally depend upon these sensor nodes, which normally consist of non-rechargeable batteries. Sometimes it processes unnecessary information with high energy consumption. If more energy consumption occurs, the network lifetime is decreased. So, how to efficiently implement the wireless sensor networks to progressively improve the network lifetime is the main aim of this proposed method. In this, a mobile element based data gathering technique is used. In this method, a tinybee is typically sent from a mobile element and comes back to the mobile element with aggregated information. Hence, the tour length of the mobile element is reduced and energy can be efficiently used than the present system. Subsequently, it decreases the delay and improves the network lifetime